2017
DOI: 10.1111/jopr.12729
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Anxiety on the Satisfaction of Dental Implant Patients

Abstract: The results of this study indicated that patient satisfaction with dental implant treatment was high in all patients. STAI-state anxiety had a greater impact on patient satisfaction than did trait anxiety. HB levels negatively affected patient satisfaction in patients with low STAI-trait and STAI-state anxiety levels. BF positively affected patient satisfaction in patients with high STAI-state anxiety levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
2
2
0
Order By: Relevance
“…This finding may reflect a good venipuncture service that phlebotomy unit has provided for the patients, which leads to a higher patient's satisfaction. This is also supported by a few other studies which reported the significant association between patients satisfaction and lower anxiety level, which can explain our study finding [17,23] In terms of the smoking status, ex-smoker group found to have a significantly lower state and trait-anxiety score compared to the current smoker group (adj. beta: 10.156 and 5.747, respectively).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding may reflect a good venipuncture service that phlebotomy unit has provided for the patients, which leads to a higher patient's satisfaction. This is also supported by a few other studies which reported the significant association between patients satisfaction and lower anxiety level, which can explain our study finding [17,23] In terms of the smoking status, ex-smoker group found to have a significantly lower state and trait-anxiety score compared to the current smoker group (adj. beta: 10.156 and 5.747, respectively).…”
Section: Discussionsupporting
confidence: 91%
“…Apart from having a well-managed flow for the patients to follow, the conducive air-conditioned room as well as patients are attended by the well-trained and friendly phlebotomists who are qualified for the venepuncture added the good quality of services here. This can be supported by other studies which found that good phlebotomy experience and satisfaction will lead to low anxiety score of the patients [17]. In addition, well-managed needle procedures may reduce the venepuncture distress significantly [18].…”
Section: Discussionsupporting
confidence: 52%
“…A large number of patients worldwide require surgical implants to replace lost teeth [ 25 ]. However, functional restoration following implantation remains a clinical challenge.…”
Section: Discussionmentioning
confidence: 99%
“…RBFDP achieve clinical outcomes in longevity in comparison with those of conventional fixed partial dentures. (2)(3)(4)(5)(6) Resin Bonded FDP was first considered as an intermediate restoration, service for a little time before being replaced by a permanent restoration. They were indicated for young patients because of their conservative preparation which poses less danger to the pulp.…”
Section: Introductionmentioning
confidence: 99%